2004
DOI: 10.1088/0953-8984/16/16/009
|View full text |Cite
|
Sign up to set email alerts
|

The structural and magnetic characterization of 6H-perovskite-type oxides Ba3LnIr2O9(Ln = Y, lanthanides)

Abstract: The crystal structures and magnetic properties of quaternary oxides Ba 3 LnIr 2 O 9 (Ln = Y, lanthanides) are reported. Rietveld analyses of their x-ray diffraction data indicate that they adopt the 6H-perovskite-type structure with space group P6 3 /mmc or, in the case of Ln = La and Nd only, a monoclinically distorted structure with space group C2/c. They have the valence state of Ba 3 Ln 4+ Ir 4+ 2 O 9 (for Ln = Ce, Pr, and Tb) or Ba 3 Ln 3+ Ir 4.5+2 O 9 (for Ln = Y and other lanthanides). Measurements of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
92
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 27 publications
11
92
0
Order By: Relevance
“…Our XRD analysis confirmed that the AP sample was formed in a hexagonal structure (P6 3 /mmc) as reported earlier 10 but we found that after high-pressure treatment the structure changed to a cubic double perovskite (Ba 2 MM'O 6 ) phase with space group Fm-3m. It is relevant to mention that Ba 3 NiSb 2 O 9 was also reported to transform from a hexagonal (P6 3 /mmc) to cubic (Fm-3m) phase when treated under 9 GPa pressure at 1273 K for 30 min.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Our XRD analysis confirmed that the AP sample was formed in a hexagonal structure (P6 3 /mmc) as reported earlier 10 but we found that after high-pressure treatment the structure changed to a cubic double perovskite (Ba 2 MM'O 6 ) phase with space group Fm-3m. It is relevant to mention that Ba 3 NiSb 2 O 9 was also reported to transform from a hexagonal (P6 3 /mmc) to cubic (Fm-3m) phase when treated under 9 GPa pressure at 1273 K for 30 min.…”
supporting
confidence: 90%
“…Ba 3 YIr 2 O 9 has a similar chemical formula like Ba 3 IrTi 2 O 9 and it crystallizes in the hexagonal structure (P6 3 /mmc) with Ir-Ir structural dimers arranged in an edge-shared triangular fashion. 10 Since all the Ir are equivalent, they should have a fractional oxidation state of +4.5 in a simple ionic picture. Our investigation of this 5d-based system is motivated by the fact that the fractional valence coupled with a geometrically frustrated lattice might lead to a spin-liquid state or possibly a heavy fermion state as in the 3d-based LiV 2 O 4 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Impurity phases such as 6L-perovskite Ba 3 LnIr 2 O 9 [25,26] were formed due to the sublimation of Ba oxides and Ir oxides. In order to decrease such impurity phases, the excess amount (~ 30 %) of BaIrO 3 [32,33] was added during sample preparation.…”
Section: Introductionmentioning
confidence: 99%